Combined osteopathy and exercise management of Achilles tendinopathy in an athlete - Ross, G.; Macfarlane, C.; Vaughan, B. (The Journal of Sports Medicine and Physical Fitness, 2018)
Mid-portion Achilles tendinopathy is a common injury in sporting populations. There is conflicting evidence about the best approach to conservative management. This report focuses on the rehabilitation of an Achilles tendinopathy utilizing osteopathic manual therapy (OMT) and a structured exercise program in a semi-professional volleyballer. The patient presented with a 4-month history of right mid-portion Achilles tendon pain that began after a lateral inversion sprain of the right ankle. The primary complaint was pain impacting the patients vertical jump performance. The patient complained of pain that was greatest in the morning and at the beginning of a training session prior to warming up. The inventory therapy was a combination of OMT. The manual therapy was complemented with a rehabilitation program. Outcomes were assessed with the Victorian Institute of Sport Assessment - Achilles (VISA-A), visual analogue scales (VAS), painful arc, London Hospital Test, soleus lunge test and maximum vertical jump. This case presented many challenging management options including a resolving right ankle lateral inversion sprain, a past history of contralateral Achilles tendinopathy and a high training load. The case demonstrated the importance of patient-centered practice. It was integral that the patient's role as a semi-professional athlete on the volleyball court was analyzed closely in order to replicate different facets of his game, so that the rehabilitation program could support a return to performance at the highest level. Once the initial deficits in mobility and strength were addressed, the rehabilitation program focus moved to injury prevention.